One Step Hydrothermal Synthesis of Magnesium Silicate Impregnated Palm Shell Waste Activated Carbon for Copper Ion Removal - Choong, Choe Earn; Lee, Gooyong; Jang, Min; Park, Chang Min; Ibrahim, Shaliza (MDPI, 2018)
Magnesium silicate impregnated onto palm-shell waste activated carbon (PPAC) underwent mild hydrothermal treatment under one-pot synthesis, designated as PPAC-MC. Various impregnation ratios from 25 to 300% of MgSiO3 onto PPAC were tested. High levels of MgSiO3 led to high Cu(II) adsorption capacity. A ratio of 1:1 (PPAC-MS 100) was considered optimum because of its chemical stability in solution. The maximum adsorption capacity of PPAC-MS 100 for Cu(II) obtained by isotherm experiments was 369 mg g−1. The kinetic adsorption data fitted to pseudo-second-order model revealed as chemisorption. Increasing ionic strength reduced Cu(II) adsorption capacity due to the competition effect between Na+ and Cu2+. In addition, PPAC-MS 100 showed sufficient adsorption capacity for the removal of Zn(II), Al(III), Fe(II), Mn(II), and As(V), with adsorption capacities of 373 mg g−1, 244 mg g−1, 234 mg g−1, 562 mg g−1, 191 mg g−1, respectively. Three regeneration studies were also conducted. PPAC-MS was characterized using Fourier Transformed Infrared (FTIR), X-Ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Field Emission Scanning Electron Microscope (FESEM). Overall, PPAC-MS 100 is a competitive adsorbent due to its high sorption capacity and sufficient regeneration rate, while remaining economical through the reuse of palm-shell waste materials.